The Role of TGF-β Signaling Pathway in Determining Small Ruminant Litter Size - Ying Han; Guiling Cao; Wenting Chen; Changfa Wang; Muhammad Zahoor Khan (Biology)
The transforming growth factor-beta (TGF-β) superfamily plays a crucial role in regulating female reproductive traits, particularly litter size, in small ruminants, such as sheep and goats. This review comprehensively examines the molecular mechanisms through which TGF-β superfamily members—including bone morphogenetic proteins (BMPs), growth differentiation factor 9 (GDF9), inhibin (INHA and INHB), and associated signaling genes—influence ovarian follicular development, ovulation rate, and ultimately, litter size. We synthesize recent findings on polymorphisms in key genes, such as BMPR1B, BMP15, GDF9, inhibins and SMADs family genes, across diverse sheep and goat breeds worldwide. The manuscript highlights how specific mutations in these genes create an intricate signaling network that modulates granulosa cell proliferation, follicular sensitivity to FSH, and the prevention of dominant follicle selection. These molecular interactions result in increased ovulation rates and larger litter sizes in prolific breeds. The gene dosage effects observed in heterozygous versus homozygous mutation carriers further illuminate the complex nature of these reproductive regulations. This improved the understanding of the genetic basis for prolificacy provides valuable insights for marker-assisted selection strategies aimed at enhancing reproductive efficiency in small ruminant breeding programs, with significant implications for improving livestock productivity and economic outcomes.